Microscopic characterization of petiole anatomy of Asteraceous taxa of Western Himalaya‐Pakistan. Issue 2 (17th September 2021) - Akhtar, Anam; Ahmad, Mushtaq; Mahmood, Tariq; Khan, Amir Muhammad; Arfan, Muhammad; Abbas, Qamar; Zafar, Muhammad; Sultana, Shazia; Batool, Rabia; Fatima, Anam; Khan, Siraj; Aman Ullah, Sher; et al.
Abstract: Petiole anatomy of 15 species of family Asteraceae was examined which aimed to investigate petiolar anatomical structures for species level identification. Shandon Microtome was used for petiole histological preparations. Both qualitative and quantitative features were studied under microscope which showed significant variation in petiole, collenchyma, parenchyma shape/size, vascular bundles arrangement/size, and vessel elements quantity. Artemisia japonica Thunb., Cirsium vulgare (Savi) Ten., Myriactis nepalensis Less., Seriphidium brevifolium Ling & Y.R.Ling, Taraxacum officinale (L.) Weber ex F.H.Wigg., and Xanthium strumarium L. showed winged petioles. Maximum length and width of upper and lower epidermis was found in Tagetes erecta L. which is 23.05 ± 0.89 μm, 24.9 ± 1.257 μm length and 21.75 ± 1.38067 μm, 22.75 ± 0.467 μm width, respectively. Petioles of Parthenium hysterophorus L. was longest one with 9.85 ± 10.45 μm while A . japonica Thunb. showed highest number of vessel elements. Maximum size of vascular bundles was found in T . erecta L. with 5.05 ± 14.25 μm. Artemisia annua L., C . vulgare (Savi) Ten, Cyanthillium cinereum (L.) H.Rob., Helianthus annus L., M . nepalensis Less., P . hysterophorus L., Senecio chrysanthemoides DC. have trichomes while Tussilago farfara L. has highest number of vascular bundles. All species have angular collenchyma type except M . nepalensis Less., P . hysterophorus L ., S . brevifolium Ling & Y.R.Ling, Tagetes minuta L ., T . officinale L., S . chrysanthemoides DC., and T . farfara L. Cluster analysis implemented that distinct plant species in cluster. Petiolar anatomical structures and taxonomic key will helpful for distinguishing Asteraceous taxa at genus and species level. This taxonomic significant investigation will also provide baseline to taxonomists for other Asteraceae studies and phylogenetic research. Abstract : Asteraceous taxa were collected from Western Himalayan region of Pakistan for petiole anatomical studies. Plants were highly productive. Study highlighted the petiole anatomical structures. Petiole anatomy will be helpful for taxonomist and also for phylogenetic research.